(NsOBRANIE SO^INENIJ W DWENADCATI TOMAH(B; s (NrASSKAZY(B; (NpOWESTI(B: [1888-1892] / s (N~ASTX (B7s - (N~EHOW(B, (NaNTON pAWLOWI^s ((NmOSKWA(B: s (NpRAWDA(B, s, 1985)
(Nw SEDXMOJ TOM WO[LI RASSKAZY(B, (NPOWESTI (B(1888 - 1892 (NGG(B.): "(NnEPRIQTNOSTX(B", "(NkRASAWYCY(B", "(NiMENINY(B", "(NpRIPADOK(B", "(NpARI(B", "(NkNQGINQ(B", "(NwORY(B" (NI DR(B. (Na TAKVE NEOPUBLIKOWANNOE(B, (NNEOKON^ENNOE(B: "(Nu zELENINYH(B", "(NpISXMO(B".s
rus
Keywords: (NpOWESTI I RASSKAZYs